2012
DOI: 10.4269/ajtmh.2012.11-0511
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Antimalaria Chemoprophylaxis in a Combat Zone

Abstract: Abstract. Compliance with malaria chemoprophylaxis by military service members (MSMs) is notoriously low, ranging from 30% to 56%. Our objective was to determine the rate of compliance and reasons for non-compliance with malaria chemoprophylaxis among healthy US MSMs in Afghanistan. An eight-question, anonymous online survey was used to collect data regarding the compliance of healthy MSMs with malaria chemoprophylaxis. E-mail surveys were sent to 1,200 MSMs; 528 (44%) MSMs completed the survey. One-time daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 10 publications
2
29
2
Order By: Relevance
“…Approximately one third of the 2013 cases among military personnel were acquired in Afghanistan. Adherence among those military personnel who reported taking any chemoprophylaxis was 22% in 2012 and was 17% in 2013.This is substantially lower than the reported adherence by U.S. service members overall (range: 49%-100%) (50,51). Reasons for these differences might include overreporting of adherence among the survey respondents and missing information on chemoprophylaxis adherence reported to NMSS or AFHSC.…”
Section: Discussioncontrasting
confidence: 43%
“…Approximately one third of the 2013 cases among military personnel were acquired in Afghanistan. Adherence among those military personnel who reported taking any chemoprophylaxis was 22% in 2012 and was 17% in 2013.This is substantially lower than the reported adherence by U.S. service members overall (range: 49%-100%) (50,51). Reasons for these differences might include overreporting of adherence among the survey respondents and missing information on chemoprophylaxis adherence reported to NMSS or AFHSC.…”
Section: Discussioncontrasting
confidence: 43%
“…Self-reported compliance with antimalarial medications among military personnel was found to be 60% among a group of Afghanistan deployers, and in one report, self-reported compliance for mefloquine (48.5%) was much lower than for doxycycline (78.4%) and other antimalarials. 38,39 However, other studies have found that compliance with mefloquine is higher than with doxycycline (American Soldiers: 80% versus 60%; Turkish troops: 61% versus 56%; Australian travelers: 78% versus 68%). [40][41][42] However, how compliance is defined is important in interpreting these findings.…”
Section: Discussionmentioning
confidence: 97%
“…2,3,[7][8][9]16 Overall rates of side effects were comparable between doxycycline and MQ, reported by roughly 30% of respondents to both drugs. Neuropsychiatric reactions, manifested largely as "vivid dreams," were the primary side effects seen here with MQ, reported by more than 20% of respondents.…”
Section: Discussionmentioning
confidence: 90%
“…Prior studies of deployed soldiers have demonstrated poor compliance with daily doxycycline prophylaxis. [7][8][9][10][11][12] Although most efficacy trials of DH and DM have shown comparable rates of GI toxicity, AE withdrawals, and noncompliance, it is important to realize that most of the safety and tolerability data are from trials powered for efficacy, not tolerability. 13 Differences in study design, end points, assessment methods, and length of follow-up complicate the comparison of the safety and tolerability of the different dosage forms of doxycycline (Table 1).…”
Section: Introductionmentioning
confidence: 99%